2016
DOI: 10.1080/10803548.2016.1165529
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of energy balance against the nutritional status of women carriers in the brickfields of West Bengal

Abstract: The Indian brick industry is an unorganized sector in which large numbers of migrant women workers are employed. A survey was conducted on 62 women workers working in different brickfields of West Bengal to assess their physiological workload, nutritional profile, total energy expenditure and energy balance. Energy intake was calculated using physiological fuel values of carbohydrate, fat and protein. From the results it is seen that 13% of the sample population falls under severe (grade III) chronic energy de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
3
10
2
Order By: Relevance
“…Therefore, it seems that the workers of higher age group find it hard to be in this profession. In contradiction to the previous studies2, 3, 5 ) , the majority of workers were found with normal BMI. This shows the better nutritional condition of brick workers in Rajasthan in contrast to some other Indian studies2, 5, 24 ) .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, it seems that the workers of higher age group find it hard to be in this profession. In contradiction to the previous studies2, 3, 5 ) , the majority of workers were found with normal BMI. This shows the better nutritional condition of brick workers in Rajasthan in contrast to some other Indian studies2, 5, 24 ) .…”
Section: Discussioncontrasting
confidence: 99%
“…Due to a lot of manual work with traditional methods and long working hours, clay brick manufacturing is a strenuous occupation in India. Findings of the present study showed that most of the labours in this sector belong to the age group of 21–30 yr, which is almost similar to the results of previously published studies2, 3, 24, 26 ) . Therefore, it seems that the workers of higher age group find it hard to be in this profession.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Arlappa et al [71] observed a very high prevalence of CED (52%) among women from Rajasthan. In a recent study, Bandyopadhyay and Sen [72] reported very high levels of CED among women working in brickfields of West Bengal. High levels of CED were reported from women belonging to different tribal populations by Bisai and Bose [73], Chakrabarty and Bharati [74], Banik [75], and Ghosh [76].…”
Section: Discussionmentioning
confidence: 95%